The Health Problems, Misconceptions and Challenges: Experiences of Slum Dweller Adolescent Girls in Bangladesh - Muhammed Muazzam Hussain (Asian Social Work Journal, 2020)
The aim of the paper is to know the health condition of adolescent girls living in the slum areas of Sylhet city, Bangladesh, understand their physical health problems, mental health issues and identify misconceptions and challenges etc. The study was based on primary sources of data; however the secondary data e.g. official documents, books, journals, policy papers etc. were used to conduct the study. The study followed qualitative research approach and the case study method to generate sufficient primary data. The study findings show that adolescent girls of slum areas face multiple health challenges including physical health problems, mental ill health, poverty etc. They suffer from different types of diseases e.g. headache, fever, cough and cold, gastric ulcer, diarrhea, asthma and allergy, jaundice, skin diseases etc. The study also highlights some misconceptions on menstruation which added another dimension of health challenges that they face in their daily lives. In addition, family poverty prevents them in taking nutritious food which is manifested in malnutrition, iron deficiency and other health complexities. Therefore, some key areas of policy recommendations are outlined for improving their health condition.